PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK SEBAGAI DETERMINAN PERILAKU PENCEGAHAN KOMPLIKASI KEHAMILAN - Aprilya Tunggo Dewi (Jurnal Medicare, 2025)
Maternal mortality in Indonesia remains quite high, particularly due to pregnancy complications that could have been prevented through promotive and preventive efforts. The Maternal and Child Health (KIA) Handbook is an educational medium designed to help pregnant women recognize danger signs and raise awareness in preventing complications, although its use is not yet fully optimal. This study aims to assess the correlation between KIA handbook utilization rates and behavior in preventing pregnancy complications. This research used a correlational analytical design, a cross-sectional approach on 49 pregnant women selected through purposive sampling at TPMB Bidan Biastike W., SST, Pasuruan Regency, East Java. Primary data were collected using a structured questionnaire and analyzed using the Spearman Rank test. The analysis results showed a significant correlation between the utilization of the KIA handbook and behavior in preventing complications (p = 0.000; r = 0.721) with a positive direction and high correlation strength. This finding confirms that the better the utilization of the KIA handbook, the better the behavior in preventing complications in pregnant women.